Chapter Monitoraggio, conservazione e informazione nella Baia Di Ieranto: un modello circolare per la gestione delle Aree Marine Protette - Eddine Said, Ala (Proceedings e report, 2020)
The 7 years monitoring-conservation-information program in the special B zone of Ieranto bay (belonging to the Marine Protected Area Punta Campanella - Naples, Italy) shows good results in terms of reducing illegal activities (such as illegal fishing, unauthorized boating, pollution and anchoring) and promoting environmental awareness for visitors. This 3-way management model represents one of the best practices of the MPA that could be applied to other MPAs in order to improve the correct usage of a protected area and to decrease/control the illegal actions and protect the environment